Analisis Efektivitas dan Efisiensi Pengelolaan Keuangan Daerah di Kabupaten Lombok Timur Selama dan Pasca Covid-19: Analysis of Effectiveness and Efficiency of Regional Financial Management in East Lombok District During and Post Covid-19 - Tasya Hilma Fadila; Abdul Manan; Eka Agustiani (Experimental Student Experiences, 2022)
This study aims to analyze the extent to which the level of Financial Effectiveness and Efficiency in the East Lombok Regency during the Covid-19 and Post-Covid-19 periods. The data used is Secondary data, namely East Lombok Regency APBD data in 2019-2021. The analysis technique used is to calculate the Regional Financial Effectiveness Ratio and Efficiency Ratio. The results obtained show that overall, the average value of the effectiveness ratio for East Lombok Regency Regional Finance in 2019-2021 reached an effective level even during the Covid-19 Pandemic. This means that the local government of East Lombok Regency has succeeded in realizing Regional Original Income (PAD) from the previously estimated target so that the potential of existing PAD can be maximized by the local government to support economic stability in East Lombok Regency. Meanwhile, the level of Regional Financial Efficiency in East Lombok Regency in 2019-2021 is at the Less Efficient and Inefficient level. This means that the portion of input use (spending) is more than 90 percent compared to the amount of output (income). In terms of the economy and finance, this is an inefficient condition, especially during the 2019-2020 Covid-19 Pandemic.